2011
DOI: 10.1115/1.4004309
|View full text |Cite
|
Sign up to set email alerts
|

Control of a Forced Impacting Hertzian Contact Oscillator Near Sub- and Superharmonic Resonances of Order 2

Abstract: The effect of a fast harmonic base displacement and of a fast periodically time varying stiffness on vibroimpact dynamics of a forced single-sided Hertzian contact oscillator is investigated analytically and numerically near sub- and superharmonic resonances of order 2. The study is carried out using averaging procedure over the fast dynamic and applying a perturbation analysis on the slow dynamic. The results show that a fast harmonic base displacement shifts the location of jumps, triggering the vibroimpact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…It was shown that the excitation from above or through base displacement shifts the resonance curve left, whereas the fast parametric stiffness shifts the response curve right. A recent study was carried out near sub-and superharmonic resonances of order 2 and similar phenomena were found [10]. The results demonstrated principally that such control techniques produce a shift and softens the system behavior.…”
Section: Introductionsupporting
confidence: 61%
“…It was shown that the excitation from above or through base displacement shifts the resonance curve left, whereas the fast parametric stiffness shifts the response curve right. A recent study was carried out near sub-and superharmonic resonances of order 2 and similar phenomena were found [10]. The results demonstrated principally that such control techniques produce a shift and softens the system behavior.…”
Section: Introductionsupporting
confidence: 61%
“…The practical way for controlling the vibroimpact dynamics of a Hertzian contact forced oscillator is the introduction of a fast harmonic base displacement, as showed by Bichri et al [11], which is generally around some microns. Different aspects of vibroimpact dynamics in a forced Hertzian contact oscillator such as the effect of time delay, control of a forced impact Hertzian contact near resonances [12], contact stiffness modulation in contact-mode atomic force microscopy [13], and the effect of EA on contact loss in a Hertzian contact oscillator [14] are intensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The super-and sub-harmonic resonance conditions along with the combination resonances, have been studied by Elnaggar and El-Basyouny [22] for the additive type of self-excited two coupled-second order systems subjected to multi-frequency excitation. These resonance conditions for the effect of fast harmonic base displacement with periodically time varying stiffness on Vibro impact dynamics of a forced single-sided Hertzian contact oscillator have been investigated by Bichri and Belhaq [23]. Davis and Rajan [24,25] discussed the random sub and superharmonic resonance conditions extensively with the help of a Duffing oscillator.…”
Section: Introductionmentioning
confidence: 99%